Croatia - Living Standards Assessment : Volume 2. Promoting Social Inclusion and Regional Equity - World Bank (Washington, DC, 2012)
The paper describes the main methodological issues underlying the estimation of poverty rates for Croatia. Volume one focuses on the construction of the consumption aggregate as a summary measure of living standards which is the summary measure used to proxy living standards. Special attention is devoted to the estimation of the consumption flow from durable goods. Volume two focuses on the estimation of the (absolute) poverty line. Both elements are at the core of the poverty measurement exercises carried out in two companion papers in this volume. This paper is organized into three sections with the first dealing with the construction of the consumption aggregate. The second section describes the choice of the equivalence scale used to adjust the consumption aggregate for differences in household composition, and the third section details the procedure used to estimate the poverty line.